Pioneer Rocketry 2015 WSGC Collegiate Rocket Competition - Ellenberger, Jake (Proceedings of the Wisconsin Space Conference, 2016)
The objective of the 2015 Wisconsin Space Grant Consortium (WSGC) Collegiate Rocket Competition was to design and build a two stage “Boosted Dart" - style rocket to achieve maximum altitude. The rocket was propelled by a single grain 54mm rocket motor (I445 Vmax). Extensive design and modeling was done to optimize the design to achieve maximum altitude. An electronic device designed to measure the rotation of the rocket that would then be correlated to rotation observed with video captured by a camera system. The rocket performed as expected in most aspects, completing most objectives per competition parameters. The flight of the boosted dart however ended in failure, as a delayed ejection of the parachute resulted in compounding failures leading to the loss of the rocket. The camera, having fallen separate from the rocket body, had survived the flight. The video was analyzed and the flights apogee was estimated to be 6000ft. The following report details the design and construction of Pioneer Rocketry’s 2015 competition rocket, along with information regarding Pioneer Rocketry’s growth as both an educational and professional organization.